The whole town's talking : a novel - Flagg, Fannie (Random House, 2016)
Lordor Nordstrom created, in his wisdom, not only a lively town and a prosperous legacy for himself but also a beautiful final resting place for his family, friends, and neighbors yet to come. "Resting place" turns out to be a bit of a misnomer, however. Odd things begin to happen, and it starts the whole town talking. With her wild imagination, great storytelling, and deep understanding of folly and the human heart, the beloved Fannie Flagg tells an unforgettable story of life, afterlife, and the remarkable goings-on of ordinary people. In The Whole Town's Talking, she reminds us that community is vital, life is a gift, and love never dies.--Provided by publisher.